(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Modern training methods in soccer training have contributed to develop of physical and skills abilities in addition to the tactical and psychological aspect and the great development of training process which clearly depends on the special basic demands in promotion preparation of event to reach ideal performance, and football game is characterized by a large number of variables and speed of performance and tactical behavior in different situations, and the problem of research was the lack of use of modern playing methods in football training, the researcher tried to build special tactical sessions according to style of fast play, to develop performance In order to develop some scientific solutions, and one of the most prominent goals of the research is to develop exercises according to the style of fast play, and to identify the impact of these exercises on the efficiency of the tactical performance in football, the research sample was represented by the youth players of Al-Nahda Football Club in the First Division League, who numbered (28) players, where divided for two groups control group and experimental group, each group included (14) junior footballers, and pre-test and a post-test were conducted to identify the results statistically, and the researcher concluded that tactical performance sessions have a positive out come to develop level of tactical aspects.